1980
DOI: 10.1063/1.1136176
|View full text |Cite
|
Sign up to set email alerts
|

Development of a high-repetition-rate mini-TEA CO2 laser

Abstract: A 1.8 cm3 active volume gas-recirculating mini-TEA CO2 laser of relatively simple design is described. The laser is capable of operating at 500 Hz with an average output of 10 W. The device is line tunable over ∼50 CO2 laser frequencies, has operated with up to 34 J/l output density and has a nearly diffraction-limited output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…[3]). A TEA-CO 2 laser, on the other hand, emits laser pulses with high output energy and a short pulse width (typically, a spike pulse with a pulse width of about 100 ns and a pulse tail of several microseconds) [4][5][6][7][8]. However, a TEA-CO 2 laser is not suitable for high-repetition operation because of the problem of poor discharge uniformity due to residual charge in the laser tube.…”
mentioning
confidence: 97%
“…[3]). A TEA-CO 2 laser, on the other hand, emits laser pulses with high output energy and a short pulse width (typically, a spike pulse with a pulse width of about 100 ns and a pulse tail of several microseconds) [4][5][6][7][8]. However, a TEA-CO 2 laser is not suitable for high-repetition operation because of the problem of poor discharge uniformity due to residual charge in the laser tube.…”
mentioning
confidence: 97%
“…Meynuk and Moulton [17] reported that a laser is in operation only for approximately 5.0X10 7 shots. The reason is due to the increase of the delay time between the auxiliary and the main discharge which cause tip erosion of the spark array of the preionizer.…”
Section: Discussionmentioning
confidence: 99%
“…A "mini-TEA" laser, operating at 500 Hz and 20 mJ/pulse, has been developed at the MIT Lincoln Laboratory . 45 We describe here a scaled-up version of the latter device, which is shown schematically in Fig. 3.…”
Section: High-repetition Rate Pulsed Tea Cc^ Lasermentioning
confidence: 99%
“…45 We describe here a scaled -up version of the latter device, which is shown schematically in Fig. 3.…”
mentioning
confidence: 99%